Modelagem da erosão hídrica dos solos na bacia hidrográfica do Córrego do Gigante – Poços de Caldas - MG - Ferreira, Adriano Mota (2019)
Hydrosedimentological processes present complex dynamics and are heavily influenced by rainfall erosivity, soil resistance to erosion and soil management. Within this context, research actions were developed on the catchment area of Gigante Stream (BHCG), due to its natural resources relevance to mining, public water supply and power generation, and which in the presence of suspended sediment, plays a big factor in efficiency reduction and operational costs increase. In this study, soil losses resulting from water erosion were estimated by means of experimental plots for soil and water loss monitoring, where the effects of soil, relief and land cover classes were assessed. In addition, the erosive power of rainfall was evaluated and water erosion was modeled by WEPP (Water Erosion Prediction Project) and RUSLE (Revised Universal Soil Loss Equation). Finally, the mass of suspended sediments transported by flood on the BHCG monitoring section, and its respective transfer rate, were also estimated. The pluvial regime presented a high degree of concentration and erosion potential. Based on the experimental plots, a loss rate of 0.623 (t ha-1 year-1) was estimated covering 50% of the BHCG area. These results served as calibration guide to the WEPP model, which allowed expansion of the coverage area to 93%, and estimation of 0.724 (t ha-1 year-1). The exposed soil areas, despite making up only 7.88% of the BHCG area, were responsible for 85.11% of the soil losses from BHCG, summing up to 108.60 t year- 1. The Hapless Cambisol Soil presented greater loss rate than that of the Red-Yellow Latosol Soil. A positive influence of the native forest and field/pasture vegetation covers was observed on the decrease of rainfall kinetic energy and consequently water erosion. The RUSLE model overestimated soil losses, since its observed values were 28 times greater than the estimated ones from the experimental plots. The mass of suspended sediment transported (MSST), estimated by the concentration of suspended sediments (CSS), was at 25.43 t year-¹, equivalent to 0.071 t ha-¹ year-¹. Sediment transfer rates were estimated in 0.23 to 11.40%, associated respectively to loss by erosion (PSEH) - estimated by the RUSLE - and experimental plots.